Impact of Capital Structure and Cash Holdings on Firm Value: Case of Firms Listed on the Ho Chi Minh Stock Exchange - Ha, Nguyen Minh; Tai, Le Minh (International Journal of Economics and Financial Issues, 2017)
This study analyses the impact of capital structure on cash holdings and the impact of capital structure and cash holdings on the value of firms listed on the Ho Chi Minh Stock Exchange (HOSE). With data from the financial statements of 105 firms listed on HOSE since 2009 – 2014 and using the GLS method, results show that cash holdings are positively related to the firm value; short - term debt is negatively related to firm value; the impact of long - term debt on the firm value is not statistically significant; short and long - term debt are negatively related to cash holdings. Keywords: Capital Structure, Cash Holdings, Firm Value JEL Classificaitons: G30, G31, G32